2017
DOI: 10.1371/journal.pone.0185612
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput m6A-seq reveals RNA m6A methylation patterns in the chloroplast and mitochondria transcriptomes of Arabidopsis thaliana

Abstract: This study is the first to comprehensively characterize m6A patterns in the Arabidopsis chloroplast and mitochondria transcriptomes based on our open accessible data deposited in NCBI's Gene Expression Omnibus with GEO Series accession number of GSE72706. Over 86% of the transcripts were methylated by m6A in the two organelles. Over 550 and 350 m6A sites were mapped, with ~5.6 to ~5.8 and ~4.6 to ~4.9 m6A sites per transcript, to the chloroplast and mitochondria genome, respectively. The overall m6A methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 60 publications
5
48
1
Order By: Relevance
“…Analyses of the relative m 6 A levels using calorimetric measurements have been previously shown to be well correlated with those of liquid MS/MS analyses (Slobodin et al , ; Engel et al , ). The data were also in agreement with previous reports by Luo et al () and Wang et al (), which suggested that the extent of m 6 A modifications in Arabidopsis organelles (i.e. chloroplasts and mitochondria) may be greater than that of nuclear‐encoded mRNAs (Shen et al , ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Analyses of the relative m 6 A levels using calorimetric measurements have been previously shown to be well correlated with those of liquid MS/MS analyses (Slobodin et al , ; Engel et al , ). The data were also in agreement with previous reports by Luo et al () and Wang et al (), which suggested that the extent of m 6 A modifications in Arabidopsis organelles (i.e. chloroplasts and mitochondria) may be greater than that of nuclear‐encoded mRNAs (Shen et al , ).…”
Section: Resultssupporting
confidence: 92%
“…These analyses further suggested that the organellar (i.e. chloroplasts and mitochondrial) transcripts may also undergo N 6 ‐methylations within various adenosine residues (Bodi et al , ; Chen and Liu, ; Luo et al , ; Shen et al , ; Wang et al , ). However, the topologies and significance of m 6 A modifications in plant organelles need to be further investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, there is tissue specificity for the m6A sites in rice callus compared with leaves (Li et al ., ). Over 86% of transcripts in the Arabidopsis chloroplast and mitochondria are m6A methylated, with 64% and 79% of m6A methylated transcription showing differential tissue expression across leaves, flowers and roots (Wang et al ., ). To understand the functional role of site‐specific m6A in mRNAs, it is necessary to determine m6A modifications in various species, cells and under external stresses.…”
Section: Function Of M6a In Plantsmentioning
confidence: 97%